Mutational Analyses of Packaging Signals in Influenza Virus PA, PB1, and PB2 Genomic RNA Segments - Liang, Yuhong (American Society for Microbiology (ASM), 2008)
The influenza A virus genome consists of eight negative-sense RNA segments that must each be packaged to produce an infectious virion. We have previously mapped the minimal cis-acting regions necessary for efficient packaging of the PA, PB1, and PB2 segments, which encode the three protein subunits of the viral RNA polymerase. The packaging signals in each of these RNAs lie within two separate regions at the 3′ and 5′ termini, each encompassing the untranslated region and extending up to 80 bases into the adjacent coding sequence. In this study, we introduced scanning mutations across the coding regions in each of these RNA segments in order to finely define the packaging signals. We found that mutations producing the most severe defects were confined to a few discrete 5′ sites in the PA or PB1 coding regions but extended across the entire (80-base) 5′ coding region of PB2. In sequence comparisons among more than 580 influenza A strains from diverse hosts, these highly deleterious mutations were each found to affect one or more conserved bases, though they did not all lie within the most broadly conserved portions of the regions that we interrogated. We have introduced silent and conserved mutations to the critical packaging sites, which did not affect protein function but impaired viral replication at levels roughly similar to those of their defects in RNA packaging. Interestingly, certain mutations showed strong tendencies to revert to wild-type sequences, which implies that these putative packaging signals are critical for the influenza life cycle.